(untitled) (Singaporean Journal of Business Economics and Management, 2024)
This study appraises the effect of dividend policy on shareholders’ wealth using a panel data of the annual reports of listed deposit money banks in Nigeria from 2011 to 2020. The Fixed Effect regression model was applied to the panel data in order to assess the influence of dividend policy on shareholder wealth in Nigeria. For the years in question, data was gathered from 15 banks’ financial statements. There is a positive and significant association between Dividend Per Share (DPS) and Shareholder Wealth, according to empirical findings. Retained Earnings (RE) and Shareholder Wealth have also been proven to have a significant positive association. Conversely, EPS has been proven to have an inverse relationship with Shareholder Wealth. As a result, it is discovered that a firm’s dividend policy has a strong negative relationship with shareholder wealth. The Dividend Relevance Theory, which claims that dividend policy has a significant impact on both shareholders’ wealth and firms’ value, was used to support the conclusion that a company’s dividend policy has an impact on its shareholders’ wealth. According to the findings of the study, companies should adopt a dividend policy that meets both shareholders’ and the firm’s investment needs. As a result, a portion of a company’s profits should be paid as dividends, while the rest should be saved for future investments.